"Remember Mother's Message" Campaign to Stop the Spread of COVID-19 in Indonesia - Remigius Asman; Fathul Qorib; Riesta Ayu Oktarina (Jurnal Spektrum Komunikasi, 2023)
This research aims to see the effectiveness of public service advertisements published by the Ministry of Education, Research, and Technology of the Republic of Indonesia's 'Remember Your Mother's'. This advertisement was launched in order to invite the public to break the chain of spread of COVID-19. The number of samples in this research was taken from students of the Communication Studies Program at Merdeka University, Brawijaya University, Tribhuwana Tunggadewi University and Gajayana University. Advertising effectiveness research use the EPIC methodology as outlined by The Nielsen Company. The EPIC paradigm comprises four dimensions: Empathy, Persuasion, Impact, and Communication. The results of this research show that the Ministry of Education, Research, and Technology of the Republic of Indonesia's 'Remember Your Mother's' campaign can have a significant impact. From these results, empathy is the most dominant dimension. The results of hypothesis testing show that the empathy variable of 91.18% has a positive sign, indicating that this variable influences audience interest. The effectiveness of advertising with empathy obtained by the most dominant indicator is the "remember mother's message campaign" advertisement in attracting students' attention which is influenced by the characteristics of the advertisement in the form of advertisements that have specific objectives and are clearly supported by advertising stages, the "remember mother's message" campaign with stages including: touching the audience's feelings to find out the level of liking for the advertisement that is shown, the level of attention of the audience towards the advertisement, whether the existing advertisement is good or not according to consumers.